2021
DOI: 10.3390/s21072293
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Classification of Blood-Like Substances Using Machine Learning Methods Combined with Genetic Algorithms in Transductive and Inductive Scenarios

Abstract: This study is focused on applying genetic algorithms (GAs) to model and band selection in hyperspectral image classification. We use a forensic-inspired data set of seven hyperspectral images with blood and five visually similar substances to test GA-optimised classifiers in two scenarios: when the training and test data come from the same image and when they come from different images, which is a more challenging task due to significant spectral differences. In our experiments, we compare GA with a classic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…A stratified k-fold cross-validation [ 32 ] with 10 fold is performed, obtaining a mean classification accuracy of 98.9% with a standard deviation of on the test dataset. This seems consistent with results in [ 8 , 9 ]. The parameters selected for the optimization are: Batch size .…”
Section: Analysis Of Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…A stratified k-fold cross-validation [ 32 ] with 10 fold is performed, obtaining a mean classification accuracy of 98.9% with a standard deviation of on the test dataset. This seems consistent with results in [ 8 , 9 ]. The parameters selected for the optimization are: Batch size .…”
Section: Analysis Of Resultssupporting
confidence: 94%
“…Both networks were trained exploiting a hyper-parameter Bayesian optimization technique and evaluated with a k-fold cross-validation method with 10 folds. It has been shown how, through the use of simple, lightweight MLP models, the performance of more complex DNN architectures can be achieved, consistent with results in [ 8 , 9 ]. The results of this study showed that this new approach can achieve high performance for all substrates under investigation, being able to obtain a reflectance spectra traceable to the reference one regardless of the surfaces involved in a hypothetical crime scene under investigation.…”
Section: Discussion and Conclusionsupporting
confidence: 81%
See 1 more Smart Citation
“…GA is considered one of the most important classes of algorithms based on biological processes. Indeed, GA is widely applied, for instance, in machine learning problems to optimize parameters and select features 31,32,47–52 . It is worth noting that other biology‐inspired algorithms are also used to solve this problem, such as elephant search optimization, artificial bee colony and gray wolf optimizer 53–55 .…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, GA is widely applied, for instance, in machine learning problems to optimize parameters and select features. 31,32,[47][48][49][50][51][52] It is worth noting that other biology-inspired algorithms are also used to solve this problem, such as elephant search optimization, artificial bee colony and gray wolf optimizer. [53][54][55] Elephant search optimization was applied in the problem of selecting features for microarray data analysis.…”
Section: Genetic Algorithmmentioning
confidence: 99%